Correlation between Admission Criteria and Academic Performance in Medical and Dental Colleges of Khyber Pakhtunkhwa - Imran Zaman Khan, Usman Mahboob, Rahila Yasmeen, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To evaluate the connection among admission criteria and academic performance amongst medical and dental scholars of different institutes of Khyber Pakhtunkhwa. Study design: Quantitative-cross-sectional study. Study setting: Department of Medical Education of Khyber Medical University, Peshawar from 15th February to 15th July 2017. Methodology: Ten thousand and sixty one students attending 10 Medical colleges of KP from entering for qualification who were registered in the 2017, 2018, 2019, 2020, 2021 and 2022 academic sessions. Results: Intermediate marks (with median =0.22) have noteworthy correlation (both at 0.05 & 0.01 points) with all 5 professional exam marks of all medical sample scholars, trailed by Merit and Entrance test (0.33 and 0.19 median marks). The relationship for merit and entrance marks was also noteworthy for all of the cases excluding for 3rd year. Conclusion: All the forecasters (intermediate, entrance test and merit marks) were meaningfully linked with all 5 MBBS examination marks of all the medical colleges, in nearly all the six units. Though, stepwise regression analysis uncovered that amongst the analysts, from 1st to 4th year, Intermediate was establish the finest analyst, tracked by merit and entrance score whereas for the fifth year; merit was the finest analyst, trailed by entrance test and Intermediate scores. Key words: Educational Testing and Evaluation Agency (ETEA), Predictive validity,